2010
DOI: 10.1128/mcb.01328-09
|View full text |Cite
|
Sign up to set email alerts
|

RAB26 and RAB3D Are Direct Transcriptional Targets of MIST1 That Regulate Exocrine Granule Maturation

Abstract: Little is known about how differentiating cells reorganize their cellular structure to perform specialized physiological functions. MIST1, an evolutionarily conserved transcription factor, is required for the formation of large, specialized secretory vesicles in gastric zymogenic (chief) cells (ZCs) as they differentiate from their mucous neck cell progenitors. Here, we show that MIST1 binds to highly conserved CATATG E-boxes to directly activate transcription of 6 genes, including those encoding the small GTP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
126
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 92 publications
(131 citation statements)
references
References 72 publications
5
126
0
Order By: Relevance
“…Peak calling on each data set was cross-referenced to identify only conserved binding regions using both MIST1 antibodies (see Materials and Methods). Consistent with previous reports on MIST1 DNA binding (18,51), CAGCTG (GC) and CATATG (TA) E-box sites were the most enriched motifs within all MIST1 peaks, with an expected enhanced distribution centered over the transcription start site (TSS), mirroring the genome-wide MIST1 binding distribution. As predicted, several previously confirmed MIST1 targets were well represented in this analysis, including members of the RAB family of cytoskeletal adapters (18) and the proapoptotic gene Htra2 (12).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Peak calling on each data set was cross-referenced to identify only conserved binding regions using both MIST1 antibodies (see Materials and Methods). Consistent with previous reports on MIST1 DNA binding (18,51), CAGCTG (GC) and CATATG (TA) E-box sites were the most enriched motifs within all MIST1 peaks, with an expected enhanced distribution centered over the transcription start site (TSS), mirroring the genome-wide MIST1 binding distribution. As predicted, several previously confirmed MIST1 targets were well represented in this analysis, including members of the RAB family of cytoskeletal adapters (18) and the proapoptotic gene Htra2 (12).…”
Section: Resultssupporting
confidence: 90%
“…MIST1's widespread transcriptional regulatory role throughout the secretory network establishes it as a key component in ensuring the proper function of these pathways. This broad role also explains, for the first time, the complex defective exocytosis phenotype associated with Mist1 KO mice (12,18,19,21,67). The transcriptional role of MIST1 during ER stress is primarily to augment the secretory pathway rather than to initiate new expression of target genes, consistent with previous classifications of MIST1 as a "scaling factor," a unique class of transcriptional regulators that serve to enhance the effects of other transcription complexes (67).…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…This issue remains to be resolved. However, another more recent study has demonstrated that the transcription factor MIST1 induces the formation of large granules in gastric chief cells by inducing expression of Rab3D and Rab26 [35]. Similarly, overexpression of mutant Rab3D interfered with the formation of Weibel-Palade bodies in platelets [36].…”
Section: Discussionmentioning
confidence: 98%
“…[31][32][33] This transition involves expression of the bHLH transcription factor MIST1, and genetic ablation in mice has demonstrated MIST1 as critically important for the structural features of the mature chief cell, including basal nuclear polarity and formation of large digestive enzyme containing granules. 28,34 In animal models, chronic Helicobacter colonization induces loss of parietal cells (ie, oxyntic atrophy) and concomitant metaplasia of the basally located chief cells. 11,31,[35][36][37] Specifically, chief cells regain proliferative potential and start reexpressing progenitor markers such as TFF2, MUC6, and the epitope for the lectin Griffonia Simplificolia, GS-II.…”
mentioning
confidence: 99%